46.5L: Late‐News Paper: Large Area Sputtered Al2O3 Films for High Mobility AM‐TFT Backplanes on PVD Array System PiVot 55kVi2. Issue 1 (1st July 2013) - Kloeppel, Andreas; Liu, Jian; Scheer, Evelyn
Abstract: The production worthiness of sputtered Al2 O3 barrier films on Gen 8.5 substrates using rotary targets on PVD array system PiVot™ is demonstrated in order to provide increased stability to IGZO AM‐OLED backplanes. The achieved Al2 O3 layer properties and uniformity illustrate the advantages of using rotary technology.